Mujeres, hombres y vida familiar en México. Persistencia de la inequidad de género anclada en la desigualdad social - Rojas, Olga Lorena (El Colegio de México A.C., 2016)
This paper offers a discussion about the analytical relevance of the crossroads between social inequality and gender to account for the wide range of possibilities of relationships between men and women in family life in Mexico. To do this, we consider the advances in social qualitative research undertaken in Mexico on the changes in the organization of family life, product of social, demographic, economic [74] and cultural changes in recent decades, as well as some theoretical proposals that have been developed on the transformation of intimacy as a result of social and cultural changes that modernity has brought in more developed societies.